Development of Leadership Transformation Module for Off-Campus Students - Rohana, Hamzah; Nurul Ain Fatehah, Baharuddin; Zuraina, Ali (IOP Publishing, 2019)
Young generation is the hope and the beneficiary for the nation's development in the future. However, in today’s world, the increase of participation among students in Higher Education Institutions (IPT) in various social problems is very disturbing. The need for serious efforts in helping students to improve the internal strength to form a strong personality and understanding of social responsibility as a leader or Caliph is not only to themselves but also for the society. This study focuses on students who live outside the campus. This is because off-campus students are not bound by the rules of the residential colleges, yet they are only bound by the regulations of the university. Besides, they are beyond of management’s control in university. Therefore, students have the tendency for being influence with negative elements from outside, if they do not do well in self-management.Through the preliminary findings, studies found that students are not able to understand, practice and carry out responsibility as a Caliph in terms of; self-management; relationship with the Creator; social relationship with housemate; and environmental management leadership. Therefore, this article discuss the process of Development of Leadership Transformation Module of Off- Campus Students (TKDPLK) by looking at the module’s content validity. This module is developed by integrating spiritual intelligence and giving awareness of social responsibility